1995
DOI: 10.1038/bjc.1995.326
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of radiation-induced cisplatin resistance in murine fibrosarcoma cells by selective modulation of the cyclic GMP-dependent transduction pathway

Abstract: Summary Cisplatin resistance, induced in murine fibrosarcoma cells (SSK) in vitro or in vivo by low-dose irradiation, can be overcome by activation of the cyclic GMP(cGMP)-dependent transduction pathway. This is mediated either by stimulating cGMP formation with sodium nitroprusside or by replacing cGMP with a selective activator of the cGMP-dependent protein kinase, 8-bromo-cGMP. The cyclic AMP-dependent transduction pathway is not involved in cisplatin resistance. Instead, activation of cAMP sensitises both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, considerable evidence has suggested that cAMP and cGMP are crucial intracellular second messengers that regulate a wide variety of cellular processes including proliferation and apoptosis . Aberrant regulation of these messengers might be an important system for CDDP resistance . Moreover, among the known PDE gene families, PDE3B is the most abundantly expressed form in human leukemia cells .…”
Section: Resultsmentioning
confidence: 99%
“…However, considerable evidence has suggested that cAMP and cGMP are crucial intracellular second messengers that regulate a wide variety of cellular processes including proliferation and apoptosis . Aberrant regulation of these messengers might be an important system for CDDP resistance . Moreover, among the known PDE gene families, PDE3B is the most abundantly expressed form in human leukemia cells .…”
Section: Resultsmentioning
confidence: 99%
“…Resistance was associated with alterations of the cGMP-dependent transduction pathway and could be overcome either by enhanced cGMP formation (Eichholtz-Wirth, 1995a) or by heat (EichholtzWirth, 1995b). It was of interest to investigate whether a similar resistance could also be induced by radiation in human cells.…”
mentioning
confidence: 99%
“…The combination of cisplatin provides a synergetic effect for radiotherapy for the reason that cisplatin could enhance the sensitivity to radiation (Boeckman et al, 2005). Interestingly, some studies have revealed that cancer cells could acquire cisplatin resistance after radiation therapy (Eichholtz-Wirth, 1995;Zhuang et al, 2019). Based on our clinical observations, the phenomenon of cisplatin resistance is commonly seen in NPC patients who also resistant to radiotherapy.…”
Section: Introductionmentioning
confidence: 70%